Analysis of saliva and gingival crevice fluid by total reflection X‐ray fluorescence (TXRF). (23rd March 2016) - Cleto, Daniele Aparecida Maia; Andrello, Avacir Casanova; Netto, Ítalo José Vitorino; Appoloni, Carlos Roberto
Abstract : The study of liquid biological samples with the use of various techniques has become a routine task nowadays. Saliva has been a study object for the correlation of chemical elements with a disorder in human body. Saliva is an aqueous hypotonic fluid and transparent and produced by various secretory glands (parotid, submandibular, sublingual, and smaller glands). This paper uses the technique of total reflection X‐ray fluorescence (TXRF) to analyze saliva samples collected in duct of the parotid gland and the gingival crevice between first (tooth 46) and second (tooth 47) grinding teeth of seven individuals. Using the TXRF technique, the main objective of this work was to assess the results obtained quali‐quantitatively. The chemical elements identified in saliva samples of the parotid gland and the gingival crevice were P, S, Cl, K, Ca, Ti, Mn, Fe, Cu, Zn, Se, Br, Rb, and Pb. Although different elements have been identified in the analyzed samples, the identified chemical elements have varied from one individual to another. Comparing the results obtained from the saliva samples of parotid gland and the gingival crevice, it could be observed in the gingival crevice other elements not found in the parotid gland. Therefore, the sampling strategy and the TXRF technique was able to differentiate chemical elements in the samples of the parotid gland and the gingival crevice. Copyright © 2016 John Wiley & Sons, Ltd.